Regulação em florestas inequiâneas sob regime de manejo florestal comunitário - Silva, Diego Armando Silva da (2014)
Planning inequiâneas logging in forests, is determined such that a portion of the forest is divided into Annual Production Unit (APU), and these, in turn, in Work Units (WUs), however in some areas community forest management in the Amazon, are established a single production unit and other units end up being established in nearby areas not belonging to the community which makes the management of a particular settlement. Thus, the production units are harvested in one year, providing the timber only income in this period. The timber income at once, is a problem for the producer, since many of them have difficulties in managing economic resources derived from community management plan, often spending or investing in resources that does not allow its socioeconomic growth. In this sense, this dissertation was developed in order to show alternative forest planning in areas under community management in the Amazon, with this search structured in two chapters. The first chapter is to propose a methodology for stratification by production and income in an area under community forestry. Volumetric stratification afforded identify areas of higher or lower productivity, so the wielder can do a better tactical planning, such as determining the number of employees, number of teams, machinery and other variables. Have stratification by income will be useful in strategic planning, in which forest managers can make the decision to explore the production units over the planning horizon, moreover, this stratification was used in the optimization model proposed in Chapter 2, exerting a strong influence in this model because it was possible to identify why certain unit was allocated in determiando year planning horizon for these reasons stratification by volume and income are useful in Chapter 2, whose goal was to simulate dynamic new crop in the area management, proposing a new drive bay management, using for this purpose a model of integer programming. In this sense, combine socioeconomic and environmental development provided by forest management with IT management in the forestry sector, represents an excellent alternative for forest planning in the areas of community management in the Amazon.